ECONOMIC DECISION-MAKING AND ITS ROLE IN THE DEVELOPMENT PROCESS: THE ECONOMIES OF RWANDA AND IRAQ (A COMPARATIVE STUDY) (World Economics and Finance Bulletin, 2026)
The process of economic decision-making is very important in drawing the economic map of every country, whether developed or developing, by identifying and diagnosing weaknesses and putting in place appropriate mechanisms to address them or reduce their repercussions and risks to the economy, Rwanda is one of the African countries that has become a model in the good making and formulation of economic decisions, especially since it was exposed in the mid-nineties to bloody and tragic events that left victims and destruction of the economic infrastructure, accompanied by the spread of diseases, ignorance, administrative corruption and the deterioration of services, However, in a short time and with limited local resources, Rwanda was able to implement its plans in various economic sectors and achieve significant progress and a major leap forward in its economic development. On the other hand, the research addressed the importance of decision-making in Iraq as a comparative study with Rwanda. Iraq, due to the recklessness of decisionmakers, was subjected to several wars over three decades, culminating in a severe economic embargo that completely halted economic development and caused a significant decline in most economic activities, However, after 2003, due to the weakness of successive governments, decision-makers were unable to improve the economic situation, leaving behind a fragile economy suffering from persistent structural imbalances, large debt, financial and administrative corruption that led to the squandering and loss of resources and the decline of development opportunities, and a weak authority dominating the country’s resources, sharing wealth, privileges and positions among themselves, which negatively affected the health, service and education situation.